Implementation of the DSN-MUI Fatwa on Product Testimonials from Istihsan Perspective - Alfa Saniyah; M. Lathoif Ghozali (Study Program Ekonomi Syari'ah, Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2023)
Today, product advertising remains a marketing strategy for both large and small businesses. In addition, testimonials or statements of satisfaction from consumers are supporting factors for new consumers to trigger purchases to be made by consumers. Fictitious testimonials are an easy step new business people use to get consumers quickly. This study aims to determine how the DSN-MUI fatwa is viewed as a legal basis and how istihsan views the problem. The research method used is library research. Primary data uses DSN-MUI fatwa, and secondary data comes from books, journal articles indexed Sinta 5 to Sinta 2, and other supporting secondary data. The results of this study show that fictitious testimonials for new sellers whose purpose is to increase customer commitment to their business and provide benefits to sellers, according to the concept of istihsan, are allowed.